Implementation of the Project Based Learning (PjBL) Model as an Effort to Increase Learning Motivation and Achievement - Bujang Rasyid (Persatuan Guru Republik Indonesia Provinsi sulawesi Tenggara, 2022)
This research was conducted at SMK Negeri 1 Batam in Class XII TOI SCH, whose students' learning abilities and motivation for the subject of entrepreneurial, creative products could have been more optimal. The purpose of this classroom action research is to find out the implementation of the project-based learning (PjBL) model as an effort to increase student motivation and learning achievement. The data collection method in this study was the triangulation technique, namely the combination of several research instruments. The data analysis method is descriptive for both qualitative and quantitative data. The research results show that participatory discussions can improve students' learning achievement. This is evident from the average score obtained in the first cycle from the initial conditions increased by 3% for learning achievement. Cycle 1 to cycle 2 increased by 23% for learning achievement. Results The average increase in learning motivation was 7.74%. The conclusion obtained from this study is that implementing the project-based learning (PJBL) model can increase students' motivation and learning achievements.